The relationship of teacher certification, work motivation, and the working period with the performance of physical education teachers of elementary schools - Christianus Yanuarli Agung Pratama; Yustinus Sukarmin (Kazimierz Wielki University, 2019)
Aim: This study aims to determine the relationship between teacher certification, work motivation, and working period with the performance of elementary school physical education teachers individually and simultanuously in the Yogyakarta West Region UPT. Methods: This research is a quantitative correlational research. The population in this study were all teachers of state and private elementary schools in the Western Yogyakarta UPT with a total of 26 teachers. Data collection was carried out using documentation, observations and questionnaires that had been tested for their validity and reliability. The data analysis technique used was product moment correlation with a significance level of 5% which was tested using the help of SPSS version 22.0. Result: The results showed that: (1) there was a relationship between teacher certification and the performance of elementary school physical education teachers in the Yogyakarta West Region UPT, as proven by the r count of 0.496; significance value 0.010